Efektivitas komunikasi pemasaran menggunakan media sosial Instagram pada UMKM Hello Decoration - Musamma, Nurfauziah Syams; Tahir, Aswar (Islamic Communication Journal, 2021)
This study aims to measure the effectiveness of Hello Decoration's marketing communications in increasing sales through Instagram social media. The method used in this study is descriptive with a quantitative approach that aims to determine the effectiveness of marketing communications implemented by Hello Decoration. While the statistical formula used is the tabulation of the frequency and the average score for each research variable. The population in this study were all followers of @hellodecoration_mks, totalling 685. While the sampling technique in this study was purposive sampling. The results of this study indicate that the statistical value for each variable is on a very effective scale, namely the awareness variable (4.34), interest variable (4.29), desire variable (4.31), decision variable (4.33), and the action variable (4,30). So that the calculation for all variables reaches a value of 4.31 which is on a very effective scale from the scale range of 4.20 to 5.00. These numbers show that Hello Decoration's marketing communications implemented through Instagram social media have proven to be very effective in persuading customers to use Hello Decoration services and customers feel happy so they want to return to using Hello Decoration services.Â